2017
DOI: 10.2147/ijn.s131602
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic activity and cytocompatibility of Au<sub>25</sub>(Capt)<sub>18</sub> clusters photoexcited by blue LED light irradiation

Abstract: Antimicrobial photodynamic therapy (aPDT) has beneficial effects in dental treatment. We applied captopril-protected gold (Au 25 (Capt) 18 ) clusters as a novel photosensitizer for aPDT. Photoexcited Au clusters under light irradiation generated singlet oxygen ( 1 O 2 ). Accordingly, the antimicrobial and cytotoxic effects of Au 25 (Capt) 18 clusters under dental blue light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…16B). 89 The following section includes discussion of several strategies to improve the 1 O 2 generation efficiency and PDT activity of Au NCs by using: (i) atomically precise size control, (ii) NIR activation for deep-tissue treatments, (iii) aggregation-induced emission (AIE), (iv) resonance energy transfer (RET), and (v) forming nanocomposites with other nanomaterials for multimodal synergistic therapy (Fig. 17).…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…16B). 89 The following section includes discussion of several strategies to improve the 1 O 2 generation efficiency and PDT activity of Au NCs by using: (i) atomically precise size control, (ii) NIR activation for deep-tissue treatments, (iii) aggregation-induced emission (AIE), (iv) resonance energy transfer (RET), and (v) forming nanocomposites with other nanomaterials for multimodal synergistic therapy (Fig. 17).…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…Previously, Miyata et al compared the biocompatibility properties of Au NCs and a conventional organic dye, MB, at clinically relevant antibacterial concentrations. 19 This study showed that exposure to MB decreased the viability of fibroblastic and osteoblastic cells; exposure to Au NCs did not. It is thus important that the cytotoxicity of organic dyes in aPDT be reduced.…”
Section: Results and Discussionmentioning
confidence: 74%
“…These studies confirmed the great potential of AuNCs as fluorescence imaging agents for cancer diagnosis. Moreover, due to their optical properties, the AuNCs can be activated by light to produce reactive oxygen species, making them good candidates as photosensitizers for photodynamic therapy of cancers [ 105 , 106 ].…”
Section: Gold Nanoparticles In Cancer Diagnosismentioning
confidence: 99%